PERCEPTIONS OF THE SENIOR CITIZENS THAT PARTICIPATE IN THE EXTENSION PROGRAMS OF THE PHYSICAL EDUCATION COURSE (Fiep Bulletin - online, 2015)
The present article shows the result of a research about extension project for sênior citezens developed by the Physical education course at Centro Universitário Feevale in Novo Hamburgo, Brazil. The main research began in 2002, when other projects of the university were investigated. These studies about projects developed by the extension program of the physical education course aim to offer a contribution to the triad teaching-research-extension of the course, focusing specially on professional development and instruction. The study here comprehended the project “Guided Walk and Hydrogymnastics” in which instructors, the general coordinator, the coordinator of the physical education course, and 23 senior citizens in the projects for more than four years participated. The methodology applied was the qualitative, interpretative one, using as instruments for data collection interviews, a questionnaire, and field observations. The results came from the triangulation of the theoretical and methodological sources as recommended by authors such as  Cauduro 2004, Molina Neto 2002, and  Arnal et al. 1992, among others. Social, cultural, and economic indicators are pointed out according to the perception of the participants.
Keywords: Extension - physical education- professional development and instruction